Benign Prostatic Hyperplasia, Metabolic Syndrome and Non‐Alcoholic Fatty Liver Disease: Is Metaflammation the Link?. Issue 16 (25th July 2016) - Russo, Giorgio Ivan; Cimino, Sebastiano; Castelli, Tommaso; Favilla, Vincenzo; Gacci, Mauro; Carini, Marco; Condorelli, Rosita A.; La Vignera, Sandro; Calogero, Aldo E.; Motta, Fabio; Puzzo, Lidia; Caltabiano, Rosario; et al.
Abstract : PURPOSE: The prevalence of prostatic inflammation (PI) is very frequent in patients affected by benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS). To investigate the relationship between prostatic inflammation (PI) and the presence of MetS and non‐alcoholic fatty liver disease (NAFLD) in a cohort of patients affected by BPH/LUTS. METHODS: We conducted a prospective study from January 2012 to June 2014 on 264 consecutive patients, who underwent transurethral resection of the prostate for bladder outlet obstruction. Metabolic syndrome (MetS) has been defined according to the International Diabetes Federation (IDF). Prior to surgery, each patient has been evaluated for the presence of MetS and NAFLD. All surgical specimens were investigated for the presence of an inflammatory infiltrate, according to the Irani score. RESULTS: The prevalence of patients affected by MetS alone was 13.8% (32/232), 13.8% (32/232) by NAFLD alone, and 42.7% (99/232) by both diseases. The rate of subjects affected by MetS + NAFLD and severe PI was significantly greater than those with only one metabolic alteration (75.8% vs. 24.2%, P  < 0.01). The multivariate logistic regression analysis revealed that FLI was independently associated with high PI (Irani score ≥ 4) (odds ratio [OR]: 1.04; P  < 0.01). Further, the combination between MetS and NAFLD was associated severe PI (OR: 4.5; P  < 0.01) while not MetS as a single alteration. CONCLUSIONS: Patients with BPH/LUTS and metabolic aberration exhibited grater PI. The coexistence of MetS and NAFLD exerted a greater detrimental effect on prostate gland by increasing severity of inflammation. Prostate 76:1528–1535, 2016 . © 2016 Wiley Periodicals, Inc.